Exalting Points of View A Discussion of Michael Fried’s Interpretation of Wittgenstein’s Contribution to Aesthetic Thought - Wittusen, Cato (The Nordic Journal of Aesthetics, 2012)
This paper discusses how Wittgenstein’s thinking informs recent conversations about art and aesthetic practice by examining his influence on the work of the noted modernist art critic, Michael Fried. Fried considers an excerpt from Wittgenstein’s Culture and Value, with a puzzling thought experiment, to help us see more clearly the Canadian artist Jeff Wall’s photographic vision and aesthetic. I consider Fried’s account of the photographic practice of Jeff Wall, especially his photograph Morning Cleaning, Mies van der Rohe Foundation (1999)